Concept Of Religious Moderation As A Society Bridge And Technical Guidance For The Making Of Handsanitizer: Konsepsi Moderasi Beragama Sebagai Jembatan Pemersatu Masyarakat Dan Bimbingan Teknis Pembuatan Handsanitizer - Adi Saingo, Yakobus; Dormalin Koroh, Tince; Givens Giliary Se’u, Windynia; Hermin; Cicilia Noach, Yuvine Marlene; Baun, Soleman (Universitas Muhammadiyah Sidoarjo, 2022)
The people in Tesbatan village are generally known as people who live in religious pluralism. However, based on a preliminary survey in field, there are quite a lot of people who do not fully understand the importance of having a the right conception in a pluralistic society. Therefore, this Community Service Activity aims to form a conception of religious moderation in the Tesbatan community as a bridge for the establishment of comunity unity and co-operation in the manufacture and production of hand sanitizers form the basic ingredients of betel leaf and citrus fruits to prevent the spread og Covid-19. Methods for implementing PKM activities include : seminars on religious moderation and technical guidance on making hand sanitizer form betel leaf and citrus fruits. This activity is carried out in three stages :preparation, material provision and evaluation. In the implementation of this activity, the average response from PKM activity participants was 3,68% with very useful criteria, meaning that this PKM activity was considered very useful for the Tesbatan village community and they increasingly understood the concept of religious moderation and could also cooperate in utilizing natural resources in the form of betel leaf plants and citrus fruits to make hand sanitizer. Form the result of this study, it is hoped that community leaders as leaders can produce a cadre of leaders from young people in Tesbatan village who have a high spirit of tolerance by respecting diversity.